The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2174/1874288201711010017
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Simple Method for Fatty Acid Profiling and Determination of ω-3 Index in Red Blood Cells

Abstract: Fatty acid profiling has become a very useful and effective tool in the diagnosis, prevention and treatment of several diseases with cardiovascular disease being particularly important. In order to arrive at accurate conclusions that would help promote the health of individuals plagued by such diseases, not only excellent laboratory methods are required, but also very important monitoring responses to treatment. Improvements in methods of fatty acid profiling in biological systems regarding safety of extractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…As a caveat, Wang and Quinn report that tocopherol preferentially partitions into PC-rich lipid domains rather than phosphoethanolamine, irrespective of the unsaturation . This headgroup dependence cannot go unnoticed when discussing vitamin E as a biological antioxidant because it has been shown that PUFA chains are more likely to be attached to a phosphoethanolamine headgroup in red blood cells. Here, we did not investigate different lipid headgroups; rather, by maintaining a constant headgroup, our data clearly illustrate a reduction in αToc volume, indicating a favorable interaction that directly correlates to chain unsaturation.…”
Section: Discussionmentioning
confidence: 74%
“…As a caveat, Wang and Quinn report that tocopherol preferentially partitions into PC-rich lipid domains rather than phosphoethanolamine, irrespective of the unsaturation . This headgroup dependence cannot go unnoticed when discussing vitamin E as a biological antioxidant because it has been shown that PUFA chains are more likely to be attached to a phosphoethanolamine headgroup in red blood cells. Here, we did not investigate different lipid headgroups; rather, by maintaining a constant headgroup, our data clearly illustrate a reduction in αToc volume, indicating a favorable interaction that directly correlates to chain unsaturation.…”
Section: Discussionmentioning
confidence: 74%
“…Association between microbiome abundance at the species (top) or genus (bottom) level and nutrient intake concentration averaged over the 3 days prior to the biological collection. Three days has previously been shown to be adequate for dietary evaluation in relation to the microbiome 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Total serum lipids were determined colorimetrically on the Ace Alera (Alpha Wasserman, Caldwell, NJ) using a kit from WAKO Diagnostics (Mountain View, CA); within-and between-assay CVs were 2.8 and 4.5%, respectively). Short and long-chain fatty acid composition of serum 23 , red blood cells 24 , and fecal samples were determined by a send-out laboratory at Duke University (Durham, NC) using quadrupole mass spectrometry (Waters Xevo TQ-S, Milford, MA) based on the work of Han, et al 25 , and it was implemented in the Duke Proteomics and Metabolomics Core Facility (DPMCF).…”
mentioning
confidence: 99%
“…1 Scalp skin surface (Koch et al, 1982); 2 Sole skin epidermis (Ansari et al, 1970);3 Normal (N), uninvolved (PU), and involved (PI) psoriatic forearm skin (Chapkin et al, 1986); 4 Erythrocyte membrane (Akinyemi et al, 2017); 5 Plasma lipids (Abdelmagid et al, 2015).…”
Section: Lipids Of Healthy Skinmentioning
confidence: 99%